ORAL HEALTH IMPLICATIONS OF ELECTRONIC NICOTINE DELIVERY SYSTEMS: A BIOCHEMICAL, CLINICAL, AND CASE-BASED REVIEW (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The increasing popularity of electronic nicotine delivery systems (ENDS), including e-cigarettes and vapes, has raised significant concerns about their impact on oral health. While frequently marketed as safer alternatives to conventional tobacco products, these devices contain nicotine, propylene glycol, vegetable glycerin, and flavoring agents, all of which may exert adverse effects on oral tissues. This review synthesizes current data on the biochemical and clinical alterations observed in users of e-cigarettes. Salivary changes include reduced buffering capacity, increased acidity, oxidative stress, and impaired antimicrobial defense mechanisms, leading to xerostomia, dysbiosis, and heightened susceptibility to caries and periodontal disease. Mucosal manifestations involve cytopathological changes, inflammatory cytokine imbalance, and increased prevalence of oral lesions such as leukoplakia, candidiasis, and stomatitis. Hard tissues are affected through demineralization, hypersensitivity, and esthetic deterioration. A documented clinical case of oral erythema multiforme in a young vape user highlights the potential for severe immunopathological reactions, which improved following cessation of vaping and local therapy. The findings underscore that vaping is not a harmless lifestyle practice but a clinically relevant risk factor for oral pathology. Timely recognition of its effects is essential for preventive strategies, patient education, and appropriate therapeutic interventions.